Development of strategy for development of machine-building enterprises of Kharkiv region - Kostin, Yuriy; Tkachova, Tetiana (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article determines that the machine-building enterprises of the Kharkiv region, which in recent years have undergone structural changes, have been affected by the development of information technology at enterprises, dramatically changing the conditions of enterprises. This forces enterprises to look for effective development strategies aimed not only at implementing their social functions, but also at increasing the degree of their independence and economic independence. Despite the significant scientific achievements of strategy theory and modeling of management processes, it should be noted that some of their important aspects remain underdeveloped. Thus, most theories of strategy go beyond its understanding as a means of maintaining competitive advantage, leaving uncertain questions about the activities of the monopolist. Accordingly, there is no holistic scientific concept of the strategy of development of machine-building enterprises. Kharkiv region is one of the leaders in domestic machine building, Kharkiv region enterprises account for 11.5% of the volume of machine building products of Ukraine, which brought the region to the 2nd position among the regions (after Zaporizhia region). In January-November 2020, machine-building enterprises sold products worth UAH 17.4 billion, which is 11.2% of industrial sales. With this in mind, state-owned machine-building enterprises will have to build their own management strategy taking into account the modern requirements of socio-economic development. It is believed that the underdeveloped system of corporate governance is one of the main reasons for the low efficiency of public entities. Defects in corporate governance lead to: - distortion of information due to the low level of transparency of business entities; - the emergence of a conflict of interest of management and the subjects of management of state property, due to the non-transparent process of appointment of management and inefficient remuneration system; - Lack of corporate governance structures such as supervisory boards and independent directors, who should effectively supervise the activities of business entities; - inconsistencies between the goals set for business entities and the lack of a clear distinction between commercial and non-commercial (socio-political) functions of business entities. This fully applies to state-owned machine-building enterprises. After all, in modern conditions, these enterprises function as government units. In the conditions of transformation of the domestic market of the machine-building enterprises the use of resources uniting the software of foreign manufacturers with domestic becomes important. Therefore, the formation of enterprise development strategy is inextricably linked with modeling the behavior of certain models with specified parameters for further effective operation of the system as a whole.